THE EFFECT OF HALAL LABEL, PRODUCT QUALITY, BRAND IMAGE, AND PROMOTION ON THE PURCHASE DECISION OF HERBAL PRODUCTS - Irwany Handayani (IAIN Surakarta, 2022)
Study this aim for know effect of halal label, quality product, image brand and promotion to decision purchase herbal product international network herbal antidote to al wahida Indonesia (HNI-HPAI) marketing area of Bolon Colomadu Karanganyar. Study this use approach quantitative with population inhabitant Bolon Colomadu village Karanganyar , sample taken with use formula slovin and technique taking sample use random sampling . Data analysis with using multiple linear regression model. Research results this by Partial influential variable only promotion whereas by Partial halal label variable , quality product , and image brand influential no significant to decision purchase HNI-HPAI products in the Colomadu Bolon Marketing Area Karanganyar.